What Might Be the Value of The Company That Changed the Course of the COVID-19 Pandemic Crisis Two Years After Pandemic? The Case of PFIZER - Alina RADU (GINGHINA); Andreea-Georgiana MINCU; Alexandru-Marian SOACATE; Corneliu Florin PARASCHIV; Daniel LAZAR (Communications of International Proceedings, 2022)
Assessing the value of a company is paramount for managerial decisions. Different analysts, as well as different business valuation methods, seldom provide the exact same value, due to future uncertainty. This is why, an investor should investigate the assumptions of different future scenarios and different approaches in order to better determine the valuation of a business. This paper aims at valuating Pfizer, Inc., one of the world’s most cited company during the last few years, due to its fundamental role in keeping the COVID-19 Pandemic under control through the vaccine developed in collaboration with BioNTech. How did the vaccine change the financial statements of the company? Two valuation methods – Discounted Cash Flow Method and Multiple Valuation Method – are used in order to determine if Pfizer is undervalued or overvalued and to conclude if the value-creation objective that it has for its shareholders is achieved.
Keywords: valuation; discounted cash flow; multiple valuation